2009
DOI: 10.1093/mp/ssp084
|View full text |Cite
|
Sign up to set email alerts
|

Copper Delivery by the Copper Chaperone for Chloroplast and Cytosolic Copper/Zinc-Superoxide Dismutases: Regulation and Unexpected Phenotypes in an Arabidopsis Mutant

Abstract: Copper (Cu) is an important mineral nutrient found in chloroplasts as a cofactor associated with plastocyanin and Cu/Zn superoxide dismutase (Cu/ZnSOD). Superoxide dismutases are metallo-enzymes found in most oxygenic organisms with proposed roles in reducing oxidative stress. Several recent studies in Arabidopsis have shown that microRNAs and a SQUAMOSA promoter binding protein-like7 (SPL7) transcription factor function to down-regulate the expression of many Cu-proteins, including Cu/ZnSOD in both plastids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 62 publications
1
77
0
1
Order By: Relevance
“…Therefore, the lower germination rate of Atcsd1 was possibly due to the complete absence of CSD1 activity in the cytoplasm. In addition, current studies of SODs indicate that the level of SOD activity required for normal growth is much lower than the actual activity level measured (Cohu et al, 2009 (Cohu et al, 2009).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, the lower germination rate of Atcsd1 was possibly due to the complete absence of CSD1 activity in the cytoplasm. In addition, current studies of SODs indicate that the level of SOD activity required for normal growth is much lower than the actual activity level measured (Cohu et al, 2009 (Cohu et al, 2009).…”
Section: Discussionmentioning
confidence: 85%
“…The CCS interacts with CSD, assisting in Cu incorporation and catalysis of disulfide bond formation, thereby resulting in an active CSD (Casareno et al, 1998;Lamb et al, 2001;Brown et al, 2004;Furukawa et al, 2004). In Arabidopsis, a single AtCCS gene product activated CSDs in the cytoplasm and chloroplast (Chu et al, 2005); however, the phenotype of the AtCCS-knockout mutant (Atccs) was found to be normal (Chu et al, 2005;Cohu et al, 2009). Similarly, a CCS-independent activation pathway for CSD was found in mice (Wong et al, 2000).…”
mentioning
confidence: 99%
“…Prior to chlorophyll fluorescence imaging analysis, plants were dark adapted for 30 min. Analysis was performed as described (Cohu et al, 2009). The F v /F m and F PSII were calculated as described (Maxwell and Johnson, 2000).…”
Section: Photochemical Efficiency Analysismentioning
confidence: 99%
“…This idea was based on the observed Cu miRNA-mediated down-regulation of several Cu proteins in Arabidopsis (Abdel-Ghany et al, 2005;Yamasaki et al, 2007;Abdel-Ghany and Pilon 2008;Dugas and Bartel, 2008;Cohu et al, 2009) as well as in Brassica species, tomato (Solanum lycopersicum), maize (Zea mays), and rice (Oryza sativa; Cohu and Pilon, 2007). However, in Arabidopsis, PC2 protein was reported to be strongly affected by Cu (Abdel-Ghany 2009), and PC protein levels were also affected by Cu in poplar (Fig.…”
Section: Pc In Young Leaves Is a Preferred Target For Cu Delivery Durmentioning
confidence: 99%
“…SPL7 is required for the up-regulation of cellular Cu uptake and assimilation mechanisms, which is highlighted by the up-regulation of the expression of the plasma membrane COPT1 Cu transporter (Yamasaki et al, 2009). On low Cu, SPL7 also is required for expression of the so-called Cu microRNAs (miRNAs; Burkhead et al, 2009), which in turn down-regulate transcripts for the Cu proteins CCS, Cu/ZnSOD1 (CSD1), and CSD2 (targets of miR398), plantacyanin (target of miR408), and several laccases (targets of miR397, miR408, and miR857; Sunkar et al, 2006;Yamasaki et al, 2007;Abdel-Ghany and Pilon, 2008;Dugas and Bartel, 2008;Cohu et al, 2009;Yamasaki et al, 2009). A Cu economy model has been hypothesized in which the miRNA-mediated mechanism saves Cu for the most essential Cu proteins, such as COX and PC, during impending deficiency (Burkhead et al, 2009, and refs.…”
mentioning
confidence: 99%